Analysis The Response of Junior High School Students In Makassar City to The Science Teaching Module - Hikmahwati Arif, Rifda Nur; Rifda Mardian Arif; Salma Samputri; Siti Nurhalisa (Mataram University, 2024)
The objectives of this study are describing to 1) Students of SMP IT Mutiara response to the use of Science Teaching Module, 2) Students of SMP Muhammadiyah Makassar response to the use of Science Teaching Module, 3) All Students response to the Science Teaching Module. This research used a quantitative approach using a descriptive methodology. The population are students of SMP IT Mutiara IT and SMP Muhammadiyah Makassar registered in the 2022–2025 academic year who use scientific teaching modules provided by the Ministry of Education and Culture are the research population. This research used random sampling techniques. The data was collected by questionnaire. The results of this study showed that 1) The response of students at SMP IT Mutiara to the science teaching module are 20% in very good category, 61% in good category, 16% in moderate category 2) The response of students at Muhammadiyah Makassar to the science teaching module are 34% in very good category, 37% in good category, 7% in moderate category and 12% in bad category 3) The response of All students in both school in this research are 27% in very good category, 49% in good category, 17% in moderate category, and 8% in bad category.